The Importance Of The Unified Text In Teaching Arabic To Non-Speakers In The Light Of Language Skills Correlation/ أهمية النص الموحد في تعليم اللغة العربية للناطقين بغيرها في ضوء ترابط المهارات اللغوية - Alkaaideh, Ala' Hussein; Othman, Mohd Ala uddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The present study aims to provide a systematic vision for teaching Arabic to non-speakers to develop the learner's educational performance and to bring the learner to the highest possible linguistic level sufficiently and efficiently. This teaching approach is represented by unifying the teaching text in light of language skills integration. The importance of this approach comes from its influential role in simplifying the process of teaching Arabic to non-speakers. The study adopted the analytical survey process, in which a questionnaire was distributed to students in the first semester of the academic year 2023/2024. The study sample consisted of 203 students studying Arabic for non-native speakers at the Language Centre at the University of Jordan. The study's results confirmed the effectiveness of unified teaching text in the light of language skills correlation. The findings also revealed the positive role of this process in enhancing the linguistic sufficiency of Arabic non-native learners. Text unity and the correlation of language skills effectively teach languages, enabling learners to promote their linguistic level sufficiently and efficiently. Therefore, the present study recommends adopting this approach in the language teaching process and raising the awareness of language teachers of the importance of it.